2018
DOI: 10.1590/0102-311x00176217
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome congênita do Zika vírus em lactentes: repercussões na promoção da saúde mental das famílias

Abstract: This article aims to discuss the impacts of the promotion of families' mental health following the diagnosis of Zika virus infection in the pregnant woman and/or congenital Zika virus syndrome (CZVS) in the infant. The study also aims to foster reflection on mother-infant bonding in this context. The study is relevant not only because there is still so much to learn about CZVS, with its enormous capacity for dispersion and many doubts as to the physical consequences and psychological impacts, but also due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 2 publications
0
11
0
2
Order By: Relevance
“…Only a few studies have explored mental health outcomes and the emotional state of women exposed to ZIKV in families carrying ZIKV-associated microcephalic children [ 13 , 24 , 25 , 26 , 27 , 28 ], all of them were performed in Brazil. There was one cross-sectional study where stress, anxiety, and depression were reported from 163 caregivers of children with microcephaly vs. 324 caregivers of healthy children [ 13 ]; another cross-sectional survey study with 50 caregivers of affected children without a comparison group [ 28 ]; and only one qualitative study based on participant observations [ 26 ]. There is also an Internet-based computer-mediated communications analysis study to understand experiences and perceptions of families with microcephalic children by videos published in Youtube [ 27 ]; one letter [ 24 ] and one commentary [ 25 ] to call for attention on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have explored mental health outcomes and the emotional state of women exposed to ZIKV in families carrying ZIKV-associated microcephalic children [ 13 , 24 , 25 , 26 , 27 , 28 ], all of them were performed in Brazil. There was one cross-sectional study where stress, anxiety, and depression were reported from 163 caregivers of children with microcephaly vs. 324 caregivers of healthy children [ 13 ]; another cross-sectional survey study with 50 caregivers of affected children without a comparison group [ 28 ]; and only one qualitative study based on participant observations [ 26 ]. There is also an Internet-based computer-mediated communications analysis study to understand experiences and perceptions of families with microcephalic children by videos published in Youtube [ 27 ]; one letter [ 24 ] and one commentary [ 25 ] to call for attention on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…28 Because it is a chronic disease, possibly without cure, listening to doubts, complaints and feelings should be emphasized by the mental health professional, who expands his gaze beyond maternal concern, redoubling the provided attention and care. 29 On the other hand, mothers from Feira de Santana (Brazil), who had children with microcephaly, came across humanized professionals, who presented this qualified listening and understanding of the psychic process experienced and, even in the face of inaccuracies, sought to convey hope and comfort. 30 The way health professionals transmitted the suspicion or confirmation on the diagnosis became remarkable in the memory of the interviewed mothers, who were able to describe the moment with rich details in their speeches.…”
Section: Discussionmentioning
confidence: 99%
“…Families of children with congenital abnormalities constantly suffer from prejudiced comments and postures (25) . Prejudice is surrounded by the child's aesthetic issues, valued by social and cultural standards and has a strong influence on the individual's behavior, given the possibilities of generating strangeness and teasing by other people, leading the subject and his family to social exclusion (40) . In this context, nurses, together with the multiprofessional team, must be prepared to identify the needs of support of these women and offer adequate support for health education, with the purpose of preparing the mother for the current reality and strengthening the affective bond with the child (20,28) .…”
Section: Discussionmentioning
confidence: 99%